Changing the Demographic Characteristics of Males with Erectile Dysfunction During the Coronavirus Disease-2019 Pandemic: A Multi-institutional Comparative Analysis with the Non-pandemic Period - Volkan Şen; Bora İrer; Mustafa Ozan Horsanalı; Mehmet Oğuz Şahin; Sedat Eğriboyun; Onur Kizer; Bilgin Öztürk; Ege Sarıkaya; Şakir Ongun; Oktay Üçer; Ozan Bozkurt; Ömer Demir (Journal of Urological Surgery, 2022)

(untitled)
Objective:This study aimed to present the impact of coronavirus disease-2019 pandemic on seeking treatment in patients with erectile dysfunction (ED) and compare the clinical characteristics, demographics, and laboratory analysis of patients with ED during and before the pandemic period.Materials and Methods:The clinical and demographic characteristics and laboratory analysis of patients with ED were compared between the time interval of March 9, 2020, to June 1, 2020, and the previous 3 months from the pandemics. The International Index of Erectile Function-5 questionnaire was used to assess ED and the results from two groups were compared.Results:A 76.4% decreased total number of outpatient clinics and a 70.9% decreased number of patients with ED was observed; however a significant increase was detected in the ratio of patients with ED to the total number of patients during the pandemic period (1.7% vs. 2.1%, p=0.008). The median age of patients was smaller in the pandemic period. Mild ED was significantly higher in the pandemic period and moderate ED was detected higher in the period before the pandemic.Conclusion:The admission rate of patients with ED has increased in the pandemic period. The patients presenting with ED during the pandemic period were younger, with milder ED symptoms.